Metáfora na LSB: debaixo dos panos ou a um palmo debaixo dos nossos narizes/Metaphors in Brazilian Sign Language: it's as well to know which way the wind blows - Sandra Patrícia de Faria (Universidade Estadual de Campinas, 2006)
Este trabalho apresenta um recorte de pesquisa-ação desenvolvida em curso de formação de professores de escola pública do DF. O corpus gerado compõe-se de fraseologismos e unidades lexicais metafóricas evidenciados no dialeto de Brasília da Língua de Sinais Brasileira (LSB) e extraídos de eventos comunicativos formais ou informais entre surdos e surdos e surdos e ouvintes. Esse corpus foi contrastado com o processo metafórico evidenciado na Língua Portuguesa (LP) e classificado segundo semelhanças e diferenças. As análises se sustentam em uma metodologia qualitativa, com abordagem etnográfica, à luz da literatura sobre língua de sinais e metáfora, bem como sob a introspecção da pesquisadora. Acredita-se que esta investigação pode contribuir para a melhor compreensão do 'mundo dos surdos' e de sua língua em uso. The present work concerns an action-research carried out in a teacher training course in a public school of the DF. It tried to identify metaphorical lexical units and fraseologisms from the Brasilia variety of Brazilian Sign Language (LSB), and then, it classified these lexical units and fraseologisms according to similarities and differences concerning the metaphorical process in LSB in contrast with Portuguese (LP). The corpus has grown out from formal or informal communicative events that include deaf in interaction with deaf people and/or deaf in interaction with hearing people. The analysis sets up on qualitative methodology and uses ethnographic approach grounded on references on Sign Language, metaphor and the researcher's introspection. This investigation is useful for understanding and analyzing deaf people's reality and language in use, and also helped us to better understand metaphorical and metonymic aspects which are salient and form the base of deaf discourse.